HARDNESS OF HYBRID PVD-PECVD W-C:H COATINGS VS. SUBSTRATE TYPE - František Lofaj; Margita Kabátová (Acta Polytechnica CTU Proceedings, 2020)
The effects of substrate on the measurement of hardness (and indentation modulus) - penetration depth profiles were investigated on hybrid PVD-PECVD W-C:H coatings made with the additions of C2H2 or CH4 using High Power Impulse Magnetron Sputtering (HiPIMS) method. The substrates involved 100Cr6 bearing steel, Al2024 aluminum alloy and (111) Si wafer. Although no clear influence of the substrate type on hardness and indentation modulus of the coatings at different acetylene and hydrogen additions was observed, when both measured properties were combined in HITEIT ratio, significant shift of HIT/EIT ratio dependencies obtained on Al alloy vs. steel and Si wafer substrates occurred. Thus, the effect of substrate type on the measurementlevaluation was confirmed.